Pengaruh Ketersediaan Dan Harga Pupuk Bersubsidi Terhadap Kesejahteraan Petani Di Desa Sengka (Studi Analisis Teori Ibnu Kaldun) - Nur Afifah Hermawan; Hasanuddin; Mega Mustika (Yayasan Al-Afif, 2025)
Subsidized fertilizer is a form of government assistance aimed at reducing the burden on farmers and increasing agricultural productivity. However, in practice, the availability of fertilizer often becomes an issue, disrupting production processes and farmers’ income. This problem is mainly caused by untimely distribution and high prices due to limited supply.This study aims to analyze the effect of subsidized fertilizer availability on farmers’ welfare in Sengka Village, Bontonompo Selatan District, Gowa Regency. A quantitative approach was employed with two independent variables, namely fertilizer availability (X1) and fertilizer price (X2), and one dependent variable, farmers’ welfare (Y). Data were collected through questionnaires distributed to 80 respondents who were active farmers.The data were analyzed using multiple linear regression to examine the extent of the influence of X1 and X2 on Y. The results showed that both independent variables had a significant effect on farmers’ welfare, both simultaneously and partially. Untimely distribution and high fertilizer prices were found to negatively affect farmers’ income and quality of life. The study was analyzed using Ibn Khaldun’s economic theory, which emphasizes the importance of fair distribution and the state’s role in ensuring public welfare.